A comparison of the outcomes of emergency medical service-witnessed cardiac arrest between intravenous access before and after cardiac arrest - Yoshinori Ito; Koichi Tanaka; Hideo Inaba (Scientific Reports)
Abstract To identify factors associated with prehospital intravenous access (IVA) in non-minor emergencies and compare the outcomes of emergency medical service (EMS)-witnessed out-of-hospital cardiac arrest (OHCA) occurring before and after IVA was established. IVA performance varied significantly among prefectures; high performance was associated with a high sensitivity of IVA for subsequent EMS-witnessed OHCA. Cases with a high likelihood of IVA before OHCA included lethal cases, those transported to tertiary emergency hospitals, and medical emergency cases. Among EMS-witnessed OHCA cases, the proportion of hospital transports outside the jurisdiction, physician presence in ambulances, and shockable initial rhythms were higher in patients who received IVA before OHCA than in those who received it afterward. Conversely, incidences of advanced airway management and adrenaline administration were lower. In a multivariate logistic regression model with an interaction test, the neurologically favourable 1-month survival rate was higher in patients who received IVA before OHCA than in those who received it afterward. The impact of IVA before OHCA was more pronounced in OHCA with presumed cardiac aetiology and was negated in cases where prehospital adrenaline was administered. Compared with IVA administered after EMS-witnessed OHCA, IVA performed before OHCA is likely associated with better outcomes.